The gender principle in law as a guarantee of equality in legal regulation - Protosavitska, Liudmyla (2023)
The development of modern Ukraine on the basis of the new forms of social relations between the sexes must be carried out in accordance with world universal standards of human rights and equality between the sexes. The article defines the need for a more specific view of gender equality. Using the historical approach and different theoretical methods, the article attempts to systematize knowledge about feminism, gender, transgender, human rights and opportunities of people. The article contains an analysis of gender discrimination and violence and defines ways of overcoming them. The study focuses on the legal aspects of equal rights and opportunities in both international legal acts and Ukrainian legislation. The paper studied how a gender approach in politics, economics and social spheres was being developed. Measures taken to ensure the equal distribution of family responsibilities, ensuring a reduction in the gender pay gap, were analyzed. The main areas of gender equality guaranteed by international and domestic law were identified as follows: equal access to management positions, access to labor market participation, elimination of occupational segregation, violence and discrimination based on gender, unpaid time off, etc. The priorities of the state gender policy for the last 5 years were investigated.